2004
DOI: 10.1093/ajcn/80.3.729
|View full text |Cite
|
Sign up to set email alerts
|

A community-based randomized controlled trial of iron and zinc supplementation in Indonesian infants: effects on growth and development

Abstract: Single supplementation with zinc significantly improved growth, and single supplementation with iron significantly improved growth and psychomotor development, but combined supplementation with iron and zinc had no significant effect on growth or development. Combined, simultaneous supplementation with iron and zinc to infants cannot be routinely recommended at the iron-to-zinc ratio used in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
156
0
21

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(179 citation statements)
references
References 41 publications
2
156
0
21
Order By: Relevance
“…The interesting result in this study was the loss of the positive effect of zinc supplementation on weight gain when iron was added in the supplement, an effect that was also found in one study in Indonesian infants (Lind et al, 2004). And, despite the fact that weight gain in the placebo group was not significantly different from the iron group, the factorial analysis indicated that iron supplementation was associated with lower WAZ and weight-for-height indexes.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The interesting result in this study was the loss of the positive effect of zinc supplementation on weight gain when iron was added in the supplement, an effect that was also found in one study in Indonesian infants (Lind et al, 2004). And, despite the fact that weight gain in the placebo group was not significantly different from the iron group, the factorial analysis indicated that iron supplementation was associated with lower WAZ and weight-for-height indexes.…”
Section: Discussionsupporting
confidence: 70%
“…A recent study also conducted in Indonesian infants with a similar design shows no impact of zinc or iron or combined ironzinc supplementation on HAZ but improvement of kneeheel length with zinc or iron supplementation alone (Lind et al, 2004). This positive effect of zinc or iron supplements on knee-heel length is not shown in the former study carried out in the same country (Dijkhuizen et al, 2001).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The foetus is totally dependent on the mother for the supply of nutrients essential to maintain its life. An optimal maternal nutritional status has been shown to reduce the risks of a preterm birth and low birth weight (1)(2)(3) , improve postnatal growth (4,5) , and reduce both maternal and infant morbidity and mortality (6)(7)(8)(9) . Despite a trend of improved infant growth in most countries due to enhanced intakes of macronutrients (10) , a low maternal nutritional status during the critical stage of foetal development subsequently contributes to growth retardation in the offspring and adverse health outcomes in later life (11) .…”
mentioning
confidence: 99%
“…Los estudios realizados en niños sin desnutrición no han encontrado cambios significativos en el crecimiento. Otros estudios han demostrado el efecto del zinc sobre la talla y el peso al suministrarlo por 12 meses o más (25,35).…”
Section: Discussionunclassified